Analisa Faktor-Faktor Kebugaran Dan Aspek Fisik Terhadap Kinerja dengan Beban Kerja Sebagai Variabel Moderasi - Gatot Priambodo; Ni Luh Putu Hariastuti (Indonesian Journal of Kinanthropology (IJOK), 2023)
Background: The importance of maintaining the stability of human resources in the Surabaya City Fire and Rescue Department, specifically for Firefighters. Methods: This research employs a quantitative research method with path coefficient analysis. Results: Based on validity and reliability tests, the results indicate that the Cronbach's Alpha values for each variable are greater than 0.7, demonstrating data reliability. Furthermore, the outer loading values in SmartPLS 3.0 are greater than 0.7, indicating valid data. Based on the path coefficient test, the Path Coefficient Results for the Physical Aspect variable to Workload have a negative direction, the Path Coefficient Results for the Physical Aspect variable to Performance have a positive direction, the Path Coefficient Results for the Workload variable to Performance have a negative direction, the Path Coefficient Results for the Fitness Factor variable to Workload have a negative direction, and the Path Coefficient Results for the Fitness Factor variable to Performance have a positive direction. Conclusions: There is a relationship between Fitness Factors, Physical Aspects, and Workload on the performance of firefighters.